Cardiovascular and safety events of PCSK9 inhibitors in statin-treated patients with cardiovascular risk: A Systematic Review and Meta-Analysis - ZHAO, Zinan; HU, Xin; ZHANG, Yatong; LIU, Deping (Journal of Pharmacy & Pharmaceutical Sciences, 2020)
Objectives: To evaluate whether proprotein convertase subtilisin/kexin type 9 inhibitor (PCSK9i) is associated with cardiovascular and safety events in statin-treated patients with cardiovascular risk. Methods: Electronic databases (Pubmed, Cochrane, MEDLINE, EMBASE, ClinicalTrials.gov) were searched through March 31, 2020. Included randomized clinical trials (RCTs) compared PCSK9i use with no PCSK9i in statin treated patients. Two investigators abstracted data and appraised risks of bias. A meta-analysis was performed to calculate risk ratios (RRs) and 95% CIs using fix-effects models. Adjudicated cardiovascular events (CVE) and adverse drug events (ADE) were defined as the primary outcome. Secondary outcomes were cardiovascular (CV) death, all-cause death, nonfatal myocardial infarction, ischemic stroke, serious ADE and injection-site reaction. Results: A total of 10 RCTs 50 053 participants were included. PCSK9i use was associated with signigicant reductions in the CVE (RR, 0.87 [95%CI, 0.83-0.91]; NNT, 54; P<0.00001; I2=0%, heterogeneity P=0.86), nonfatal myocardial infarction (RR, 0.86 [95% CI, 0.78-0.96]; NNT, 95; P=0.005; I2=0%, heterogeneity P=0.88), and ischemic stroke (RR, 0.75 [95%CI 0.64-0.87]; NNT, 244; P=0.00; I2=0%, heterogeneity P=0.82) compared with no PCSK9i in statin-treated patients with CV risk. No significant associations were found between PCSK9i use and no PCSK9i in ADE and serious ADE. PCSK9i use was associated with signigicant increasing in injection-site reaction (RR, 1.55 [95%CI 1.38-1.75]; NNT, 101; P<0.00001; I2=0%, heterogeneity P=0.44). Conclusions: Among statin-treated patients with CV risk, the use of PCSK9i was associated with improving CV outcomes. The use of PCSK9i was well tolerated, but had significantly injection-site reactions.